2024
DOI: 10.1002/zamm.202300536
|View full text |Cite
|
Sign up to set email alerts
|

Influences of blowing and internal heating processes on steady MHD mixed convective boundary layer flows of radiating titanium dioxide‐ethylene glycol nanofluids

Abderrahim Wakif,
Ahmed Alshehri,
Taseer Muhammad

Abstract: The present analysis intends predominantly to explore the multiple behaviors of radiating ethylene glycol‐based titanium dioxide nanofluids during their steady boundary layer flows near a vertical permeable surface under the prominent impacts of uniform blowing and nonuniform internal heating processes. By incorporating the dynamical contribution of Lorentz and buoyancy forces in the momentum equation and adopting the single‐phase nanofluid approach along with the constitutive equations of the second‐grade rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…Some key investigations related to the fluidic system performance are described in the refs. [11][12][13]. The authors found very interesting heat transfer results for various sorts of nanofluids and suggested these as better for numerous engineering applications.…”
Section: Introductionmentioning
confidence: 95%
“…Some key investigations related to the fluidic system performance are described in the refs. [11][12][13]. The authors found very interesting heat transfer results for various sorts of nanofluids and suggested these as better for numerous engineering applications.…”
Section: Introductionmentioning
confidence: 95%